Impacts of P2P accommodation: Neighbourhood perspectives - Farmaki, Anna; Stergiou, Dimitrios P. (My University, 2019)
Peer-to-peer (P2P) accommodation has grown exponentially, yielding significant economic, social and environmental impacts. Unsurprisingly, calls for strengthening regulatory controls regarding P2P accommodation have intensified in recent years. Although research on the associated impacts of the growth of P2P accommodation has started to proliferate, minimal attention has been placed on the perceptions of residents. This study examines the impacts of P2P accommodation at the neighbourhood and residential levels by drawing from the perceptions of residents of Koukaki, a southeast neighbourhood of the Municipality of Athens, Greece which in recent years has witnessed a dramatic increase in P2P accommodation listings. The study identifies the perceived benefits and problems brought about on neighbourhoods as a result of the rapid growth of P2P accommodation in residential areas. Overall, findings are informative of the implications of the rise of P2P accommodation in residential areas and are, thus, useful to tourism planners, developers and policymakers.
Keywords: Impacts; Neighbourhoods; P2P accommodation; Resident perceptions